2015
DOI: 10.1007/s00345-015-1482-y
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year single-centre experience with three different surgical procedures of nerve-sparing cystectomy in selected organ-confined bladder cancer patients

Abstract: NS-RC for male patients accounted for 7.4 % of overall radical cystectomy. To a limited extent of the selected organ-confined bladder cancers treated, the three different procedures analysed showed comparable results in terms of local recurrence and cancer-specific survival. Both CS-C and SS-CP procedures provided excellent functional outcomes when compared to original NS-CVP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…The long‐term impact of any attempt at NS found in the present analysis confirms our earlier results after a follow‐up <3 years, where NS was shown to positively affect both day‐ and night‐time continence, with NS resulting in a 40% higher continence rate . In further support of our findings, Colombo et al reported 89% and 57% day‐ and night‐time continence rates, respectively, at 24 months’ after NS RC compared to 78% and 55% after no‐NS RC. The large discrepancy in group size hampered statistical analyses and thus precluded definitive conclusions .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The long‐term impact of any attempt at NS found in the present analysis confirms our earlier results after a follow‐up <3 years, where NS was shown to positively affect both day‐ and night‐time continence, with NS resulting in a 40% higher continence rate . In further support of our findings, Colombo et al reported 89% and 57% day‐ and night‐time continence rates, respectively, at 24 months’ after NS RC compared to 78% and 55% after no‐NS RC. The large discrepancy in group size hampered statistical analyses and thus precluded definitive conclusions .…”
Section: Discussionsupporting
confidence: 92%
“…In further support of our findings, Colombo et al reported 89% and 57% day‐ and night‐time continence rates, respectively, at 24 months’ after NS RC compared to 78% and 55% after no‐NS RC. The large discrepancy in group size hampered statistical analyses and thus precluded definitive conclusions . In addition, a parallel can be drawn with patients who underwent RP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With the aim to improve sexual and functional outcomes, several prostate-sparing cystectomy techniques have been proposed [3][4][5][6]. However, the high incidence and potentially poor prognosis of urothelial carcinoma involvement of the prostate (UPI) makes these approaches too risky for widespread use [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…nerve sparing cysto-vesicleprostatectomy [5] , capsulesparing cystectomy [6], and intrafascial seminal vesiclessparing cysto-prostatectomy [7] . Despite their functional promises, these procedures remain underutilized as the oncological-related outcomes can be serious.…”
mentioning
confidence: 99%